Independent and Interactive Effects of Habitually Ingesting Fermented Milk Products Containing Lactobacillus casei Strain Shirota and of Engaging in Moderate Habitual Daily Physical Activity on the Intestinal Health of Older People - Aoyagi, Yukitoshi; Amamoto, Ryuta; Park, Sungjin; Honda, Yusuke; Shimamoto, Kazuhito; Kushiro, Akira; Tsuji, Hirokazu; Matsumoto, Hoshitaka; Shimizu, Kensuke; Miyazaki, Kouji; Matsubara, Satoshi; Shephard, Roy J. (Frontiers in Microbiology, 2019)
Infrequent bowel movements decrease the number of beneficial bacteria in the human intestines, thereby potentially increasing the individual’s risk of colorectal cancer. The correction of such bowel problems could therefore make an important contribution to improving population health- and quality-adjusted lifespan. We examined independent and interactive effects upon the fecal microbiota of two potentially favorable determinants of intestinal motility: the intake frequency of a fermented milk product containing Lactobacillus casei strain Shirota (LcS) and the quantity/quality of habitual physical activity in 338 community-living Japanese aged 65-92 years. Subjects were arbitrarily grouped on the basis of questionnaire estimates of LcS intake (0-2, 3-5 and 6-7 days/week) and pedometer/accelerometer-determined patterns of physical activity (<7000 and ≥7000 steps/day, or <15 and ≥15 min/day of activity at an intensity >3 metabolic equivalents [METs]). After adjustment for potential confounders, the respective numbers of various beneficial fecal bacteria tended to be larger in more frequent consumers of LcS-containing products, this trend being statistically significant (mostly P<0.001) for total Lactobacillus, the Lactobacillus casei subgroup and the Atopobium cluster; in contrast, there were no statistically significant differences in fecal bacterial counts between the two physical activity groups. A multivariate-adjusted logistic regression analysis estimated that the risk of infrequent bowel movements (arbitrarily defined as defecating ≤3 days/week) was significantly lower (P<0.05) in subjects who ingested LcS-containing products 6-7 rather than 0-2 days/week (odds ratio [95% confidence interval] 0.382 [0.149-0.974]) and was also lower in those who took ≥7000 rather than <7000 steps/day (0.441 [0.201-0.971]) or spent ≥15 rather than <15 min/day of physical activity at an intensity >3 METs (0.412 [0.183-0.929]). The risk of infrequent bowel movements in subjects who combined 6-7 days/week of LcS with ≥7000 steps/day or ≥15 min/day of activity at >3 METs was only a tenth of that for individuals who combined 0-2 days/week of LcS with <7000 steps/day or <15 min/day at >3 METs. These results suggest that elderly individuals can usefully ingest LcS-containing supplements regularly (≥6 days/week) and also engage in moderate habitual physical activity (≥7000 steps/day and/or ≥15 min/day at >3 METs) in order to enhance their gastrointestinal health.